Effects of radiotherapy on salivary gland function in patients with head and neck cancers - Chia-Yung Lin; Shine-Shine Ju; Jean-San Chia; Chin-Hao Chang; Ching-Wen Chang; Min-Huey Chen (Elsevier, 2015)
Background/purpose: We explored changes in salivary gland function of head-and-neck cancer patients after radiotherapy, including pH of saliva, stimulated salivary flow rate, and saliva buffering capacity. The pH of saliva included that of parotid gland, submaxillary gland, and total resting saliva. We also investigated whether the acidity of dental plaque lowered pH of saliva. Materials and methods: From a total of 62 patients, 11 had repeated measurements taken before and every month after radiotherapy. The remaining 51 patients had a single measurement taken after radiotherapy. Seven normal patients served as the control group. Results: In the repeated measurement group, all examinations decreased dramatically in the 1st month after radiotherapy (P < 0.0001), and recovered from the 3rd month to the 6th month, but the flow rate could not return to pretreatment level. In the single measurement group, unilabiate linear regression analysis showed that the time-period after radiotherapy was a significant predictor influencing the pH of the submaxillary gland and total resting saliva. Pearson correlation coefficient analysis showed that the pH of dental plaque had a positive linear correlation with that of saliva. Concerning the influence of time-period, within 1 year after radiotherapy, all examinations were dropped. After 1 year the pH of resting saliva and plaque began to increase over time. The stimulated flow rate, pH of stimulated saliva, and buffering capacity, dropped < 1 year after radiotherapy group, increased 1-5 years after radiotherapy group, but dropped again > 5 years after radiotherapy group. Conclusion: Our results indicated that oral hygiene care is important especially during the early period after radiotherapy.